Protective Effects of Crocetin against Radiation-Induced Injury in Intestinal Epithelial Cells. (9th September 2020) - Zhang, Chen; Chen, Kequan; Wang, Jinghua; Zheng, Zhongwen; Luo, Yujun; Zhou, Weijie; Zhuo, Zewei; Liang, Jun; Sha, Weihong; Chen, Hao
Abstract : Background and Aims . Treatment options for radiation-induced intestinal injury (RIII) are limited. Crocetin has been demonstrated to exert antioxidant, antiapoptotic, and anti-inflammatory effects on various diseases. Here, we investigate the effects of crocetin on RIII in vitro . Materials and Method . IEC-6 cells exposed to 10 Gy of radiation were treated with different doses of crocetin (0, 0.1, 1, 10, and 100  μ M), and cell viability was assessed by CCK-8. The levels of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), malondialdehyde (MDA), myeloperoxidase (MPO), tumor necrosis factor- α (TNF- α ), interleukin-1 β (IL-1 β ), and interferon- γ (IFN- γ ) in culture supernatants were measured using colorimetric and ELISA kits, respectively. Cellular apoptosis was evaluated by Annexin V/PI double staining. Results . Crocetin dose-dependently improved the survival of irradiated IEC-6 cells with the optimal dose of 10  μ M, as indicated by the reduction of cellular apoptosis, decreased levels of MDA, MPO, and proinflammatory cytokines (TNF- α, IL-1 β, and IFN- γ ), and increased activities of antioxidative enzymes (SOD, CAT, and GPx). Conclusion . Our findings demonstrated that crocetin alleviated radiation-induced injury in intestinal epithelial cells, offering a promising agent for radioprotection.